Supplementary Table 2 from Monounsaturated and Diunsaturated Fatty Acids Sensitize Cervical Cancer to Radiation Therapy - Naoshad Muhammad (14960127) (2025)
Tumor growth kinetics of TC-1 orthograft tumors